2017
DOI: 10.1177/0539018417744680
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural approach to eating together: Practices of commensality among French, German and Spanish young adults

Abstract: This article explores commensal practices of French, German and Spanish young adults. In doing so, it aims to fill a gap in research on commensality and on contemporary eating practices in Europe within a qualitative cross-cultural approach. The different nationalities of the informants, along with their country of residence, contribute to emphasizing cultural diversity and laying the foundations for the highlighting of poignant differences between French, German and Spanish young people, particularly in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…Among the identified papers on commensality assessment, 51 papers were categorized as qualitative. These were put into subcategories, such as qualitative interviews ( Table 2 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] and ethnological studies ( Table 3 ) [ 42 , 43 , 44 , 45 , 46 , 47 ], log book plus interview ( Table 4 ) [ 48 , 49 , 50 , 51 ] case studies ( Table 5 ) [ 52 , 53 ] and diverse methods ( Table 6 ) [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the identified papers on commensality assessment, 51 papers were categorized as qualitative. These were put into subcategories, such as qualitative interviews ( Table 2 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] and ethnological studies ( Table 3 ) [ 42 , 43 , 44 , 45 , 46 , 47 ], log book plus interview ( Table 4 ) [ 48 , 49 , 50 , 51 ] case studies ( Table 5 ) [ 52 , 53 ] and diverse methods ( Table 6 ) [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , …”
Section: Resultsmentioning
confidence: 99%
“…The first one studying commensality to understand a phenomenon within meals, and the second to examine how to understand commensality from a meal point of view. Several papers revealed aspects of different social meanings attached to food and commensality, as well as how meaning seems to have changed over time [ 27 , 36 , 51 ]. There was also some variations around the concept, such as; commensal space, meal, eating practice, conviviality, convivial dining [ 18 , 45 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a survey on 3000 French adults reported that 42% declared having pre-meal drinks (“ apéritif ”) more often during than before the lockdown ( Darwin Nutrition & IFOP, 2020 ). Pre-meal drinks are usually the first part of a meal, opening a social eating time and are often accompanied by finger foods ( Danesi, 2018 ). The deterioration of nutritional quality during the lockdown may be partly due to increased number of social and festive eating occasions within the home, associated with consumption of low-nutritional-quality foods (e.g., sweet-tasting beverages and alcoholic beverages, processed meat, sugary foods).…”
Section: Discussionmentioning
confidence: 99%